Analysis of Psychometric Properties of the University of California, Los Angeles Loneliness Scale Version-3 (UCLA LS-V3) in the Indian Context - Sharma, Rashmi; Gupta, Jyoti (Journal of Pedagogy and Education Science, 2025)
The UCLA Loneliness Scale Version 3 (UCLA LS-V3) is the most widely utilized measure globally, with various iterations tailored to different cultural contexts. While initially conceived as unidimensional, the scale has been subject to both unidimensional and multidimensional interpretations. However, research on loneliness among Indian university students remains limited. This study investigates the psychometric properties of the UCLA LS-V3 in this population, revealing five distinct dimensions through exploratory factor analysis (EFA) and confirming construct validity through confirmatory factor analysis (CFA). The findings affirm the scale's suitability for assessing loneliness among Indian university students, contributing to the growing body of literature.